Antibiotic Use and Misuse in Dentistry in India-A Systematic Review - Aarthi Bhuvaraghan; Rebecca King; Harriet Larvin; Vishal R. Aggarwal (MDPI AG, 2021)
Background: Infections caused by antibiotic resistance pose a serious global health threat, undermining our ability to treat common infections and deliver complex medical procedures. Antibiotic misuse, particularly in low--middle-income countries, is accelerating this problem. Aim: The aim of this systematic review was to investigate the use and misuse of antibiotics in dentistry in India. Method: We included studies carried out on Indian populations evaluating the prescription of prophylactic or therapeutic antibiotics by dental practitioners or other healthcare providers, along with antibiotic self-medication by the general population. The primary outcome measure was prescription rate/use of antibiotics for dental/oral problems. The secondary outcome measures included indications for antibiotic use in dentistry, their types and regimens, factors influencing practitioners' prescription patterns and any differences based on prescriber and patient characteristics. Multiple databases were searched with no restrictions on language or publication date. The quality assessment of all included studies was carried out using the AXIS tool for cross-sectional studies and the Joanna Briggs Institute checklist for qualitative studies. Results: Of the 1377 studies identified, 50 were eligible for review, comprising 35 questionnaire surveys, 14 prescription audits and one qualitative study (semi-structured interviews). The overall quality of the included studies was found to be low to moderate. The proportion of antibiotic prescriptions amongst all prescriptions made was found to range from 27% to 88%, with most studies reporting antibiotics in over half of all prescriptions; studies also reported a high proportion of prescriptions with a fixed dose drug combination. Worryingly, combination doses not recommended by the WHO AWaRe classification were being used. The rate of antibiotic self-medication reported for dental problems varied from 5% to 35%. Conclusions: Our review identified the significant misuse of antibiotics for dental diseases, with inappropriate use therapeutically and prophylactically, the use of broad spectrum and combination antibiotics not recommended by WHO, and self-medication by the general population. There is an urgent need for targeted stewardship programmes in this arena.